Amphoteric porous membrane for all-vanadium redox flow battery and preparation method of amphoteric porous membrane

By grafting, oxidizing and Schiff base reaction on the polytetrafluoroethylene film, an amphoteric porous membrane was prepared, which solved the problems of high permeability of vanadium ion and low proton transport efficiency in all vanadium flow batteries, and achieved battery performance promote.

CN119264514AInactive Publication Date: 2025-01-07HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411784861.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In all-vana flow batteries, the high vanadium ion permeability of the existing cationic membrane leads to a decrease in battery performance, while the high vanadium resistance and low proton transmission efficiency of the anion membrane lead to a decrease in battery efficiency, lacking both low vanadium ion permeability and high vanadium ion permeability. Proton transport rate separator.

Method used

By using the preparation method of amphoteric porous membrane, grafting, oxidation and Schiff base reaction of polytetrafluoroethylene membrane, silane and aminoimidazole are introduced to form a membrane with amphoteric characteristics, and the membrane pore size and membrane charge are regulated to reduce the Vanadium ions migration and enhance proton transport.

Benefits of technology

It achieves a significant reduction in the permeability of vanadium ions while ensuring the proton transmission efficiency, and improves the battery's energy efficiency, Coulomb efficiency, voltage efficiency and capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264514A_ABST
    Figure CN119264514A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-vanadium redox flow battery diaphragms, and discloses a preparation method of an amphoteric porous membrane for an all-vanadium redox flow battery, and the preparation method comprises the following steps: carrying out active treatment on a PTFE porous membrane in plasma treatment equipment; sulfydryl silane is grafted on the surface of the membrane and is oxidized, so that the membrane has an acidic functional group; aminoimidazole is grafted to the membrane through Schiff base reaction, so that the membrane has basic groups. The amphoteric porous membrane for the all-vanadium redox flow battery prepared by the invention has amphoteric property, can have both low vanadium ion permeability and high proton transmission rate, and improves the energy efficiency of the battery; amphoteric functional groups are introduced to the PTFE porous membrane by adopting a grafting method, so that the pore size of the membrane can be adjusted, and the coulombic efficiency of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of all-vanadium liquid flow battery diaphragms, and specifically relates to an amphoteric porous membrane for an all-vanadium liquid flow battery and a preparation method thereof. Background Art

[0002] In the all-vanadium liquid flow battery system, the role of the diaphragm is to prevent the cross-mixing of positive and negative electrolytes and prevent the battery from short-circuiting. A diaphragm with excellent performance can effectively avoid solution contamination caused by cross-penetration of positive and negative electrolytes, inhibit the occurrence of self-discharge, and improve battery efficiency. The perfluorosulfonic acid membrane commonly used in all-vanadium liquid flow batteries is a cationic membrane with excellent chemical and mechanical properties, but due to its own swelling and large cluster radius, it has a high vanadium ion permeability, resulting in a decrease in battery performance; and the anion membrane has a high vanadium resistance rate and low proton transfer efficiency due to the Donan effect, which leads to an increase in membrane resistance and a decrease in battery efficiency.

[0003] Considering that the amphoteric ion exchange membrane can combine the characteristics of the cation exchange membrane and the anion exchange membrane, that is, the polymer structure of the amphoteric ion exchange membrane has both acidic functional groups to ensure the transmission of ions and alkaline functional groups to block the passage of vanadium ions, it is urgent to develop an amphoteric porous membrane for all-vanadium redox flow batteries with low vanadium ion permeability and high proton transmission rate and its preparation method. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides an amphoteric porous membrane for an all-vanadium liquid flow battery and a preparation method thereof.

[0005] The present invention specifically adopts the following technical solutions: An amphoteric porous membrane for an all-vanadium liquid flow battery and a preparation method thereof are carried out according to the following steps: S1: The polytetrafluoroethylene membrane (PTFE) is cleaned with anhydrous ethanol to remove grease and wax on the membrane surface, and the cleaned membrane is naturally dried in the air. The dried membrane is placed in a plasma treatment device for activation treatment in an air atmosphere to obtain an activated polytetrafluoroethylene membrane; S2: dissolving mercaptosilane in an organic solvent to prepare a grafting monomer solution, immersing the activated polytetrafluoroethylene membrane in the grafting monomer solution to carry out a grafting reaction, removing the residual liquid on the membrane surface after the reaction is completed, immersing the grafted membrane in an oxidant aqueous solution for oxidation, removing the residual liquid on the membrane surface after the oxidation is completed, and obtaining an acidic grafted polytetrafluoroethylene membrane; S3: The acidic grafted polytetrafluoroethylene membrane is immersed in an aminoimidazole solution to carry out a Schiff base reaction. After the reaction is completed, the liquid on the membrane surface is removed to complete the preparation of the amphoteric porous membrane.

[0006] Preferably, in step S1, the activation treatment power is 25W~100W, the time is 30S~200S, and the air flow rate is 10~50cm 3 / min.

[0007] Preferably, in step S2, the mercaptosilane is one of 3-mercaptopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane, with a mass concentration of 1% to 9%; the organic solvent is one of N,N-dimethylacetamide (DMF) and N,N-dimethylformamide (DMAc); and the oxidant is one of hydrogen peroxide and potassium permanganate, with a mass concentration of 10% to 30%.

[0008] Preferably, in step S2, the grafting reaction time is 2h~8h, and the temperature is 30°C~60°C; the oxidation reaction time is 6h~18h, and the temperature is 50°C~90°C.

[0009] Preferably, in step S3, the aminoimidazole is one of 1-(3-aminopropyl)imidazole solution; histamine solution; 1,4-dimethyl-5-aminoimidazole hydrochloride solution; 1,5-dimethyl-4-aminoimidazole hydrochloride solution, and the mass concentration is 2% to 10%.

[0010] Preferably, in step S3, the grafting reaction time is 2-8 hours and the temperature is 50-90°C.

[0011] A zwitterionic porous membrane for an all-vanadium liquid flow battery is prepared by any of the above-mentioned methods for preparing a zwitterionic porous membrane for an all-vanadium liquid flow battery.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention modifies the PTFE membrane through grafting reaction, oxidation reaction and Schiff base reaction, so that the modified PTFE membrane has amphiphilicity, which can greatly reduce the migration of vanadium ions while ensuring the proton transmission efficiency, thereby improving the energy efficiency of the battery.

[0013] 2. The present invention introduces silane into the PTFE membrane system by a grafting method, and regulates the membrane pore size by the grafting entanglement of silane in the membrane pores, thereby further reducing the permeability of vanadium ions and improving the coulombic efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram of an amphoteric porous membrane for an all-vanadium liquid flow battery and a preparation method thereof according to the present invention; Figure 2 is the infrared spectrum of the membrane surface prepared in Comparative Example 1; Figure 3 is the zeta potential on both sides of the membrane prepared in Comparative Example 2; Figure 4 is the zeta potential on both sides of the membrane prepared in comparative example 3. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0016] like Figure 1 As shown, an amphoteric porous membrane for an all-vanadium liquid flow battery and a preparation method thereof, comprising the following steps: S1: The PTFE membrane is cleaned with anhydrous ethanol to remove the grease and wax on the membrane surface. The cleaned membrane is naturally dried in the air. The dried membrane is placed in an air chamber with an activation power of 25~100W and an air flow of 10~50cm 3 / min plasma treatment equipment for activation for 30~200S; S2: Dissolve mercaptosilane in an organic solvent to prepare a grafting monomer solution with a mass concentration of 1% to 9%, immerse the activated PTFE in the grafting monomer solution, and carry out the grafting reaction at a temperature of 30 to 60°C. After 2 to 8 hours, the reaction is completed, and the residual liquid on the membrane surface is removed. The grafted membrane is immersed in an oxidant aqueous solution with a mass concentration of 10% to 30%, and an oxidation reaction is carried out at a temperature of 50 to 90°C. After 6 hours to 18 hours, the oxidation reaction is completed, and the residual liquid on the membrane surface is removed to obtain a PTFE membrane grafted with an acidic functional group; S3: The acidic grafted PTFE membrane is immersed in an aminoimidazole aqueous solution with a mass concentration of 2% to 10% to carry out a Schiff base reaction at a reaction temperature of 50 to 90°C. After 2 to 8 hours, the reaction is completed and the liquid on the membrane surface is removed to complete the preparation of the amphoteric porous membrane.

[0017] Example 1: Using the following scheme S1: The PTFE membrane was cleaned with anhydrous ethanol to remove the grease and wax on the membrane surface. The cleaned membrane was naturally dried in the air. The dried membrane was placed in a vacuum oven with a power of 25W and an air flow of 50cm 3 / min plasma treatment equipment to perform activation treatment, and after 200S, an activated PTFE membrane is obtained; S2: 3-mercaptopropyltriethoxysilane was dissolved in DMAc to prepare a grafting monomer solution with a mass concentration of 1%, and the activated PTFE membrane was immersed in the grafting monomer solution, and the grafting reaction was carried out at a temperature of 30°C. After 8 hours, the grafting reaction was completed, and the residual liquid on the membrane surface was removed. The grafted membrane was immersed in a hydrogen peroxide solution with a mass concentration of 10%, and an oxidation reaction was carried out at a temperature of 90°C. After 6 hours, the oxidation reaction was completed, and the residual liquid on the membrane surface was removed to obtain an acid-grafted PTFE membrane; S3: The acid-grafted PTFE membrane is immersed in a 2% mass concentration 1-(3-aminopropyl) imidazole aqueous solution for Schiff base reaction at 50°C for 8 hours. After the reaction is completed, the liquid on the membrane surface is removed to complete the preparation of the amphoteric porous membrane.

[0018] Example 2: Using the following scheme S1: The PTFE membrane was cleaned with anhydrous ethanol to remove the grease and wax on the membrane surface. The cleaned membrane was naturally dried in the air. The dried membrane was placed in a vacuum oven with a power of 100 W and an air flow of 10 cm 3 / min plasma treatment equipment to perform activation treatment, and after 30S, an activated PTFE membrane is obtained; S2: 3-mercaptopropyltrimethoxysilane was dissolved in DMF to prepare a grafting monomer solution with a mass concentration of 9%, and the activated PTFE membrane was immersed in the grafting monomer solution, and the grafting reaction was carried out at a temperature of 70°C. After 2 hours, the grafting reaction was completed, and the residual liquid on the membrane surface was removed. The grafted membrane was immersed in a potassium permanganate aqueous solution with a mass concentration of 30%, and an oxidation reaction was carried out at a temperature of 50°C. After 18 hours, the oxidation reaction was completed, and the residual liquid on the membrane surface was removed to obtain an acid-grafted PTFE membrane; S3: The acid-grafted PTFE membrane is immersed in a histamine aqueous solution with a mass concentration of 10% to carry out a Schiff base reaction at 90° C. for 2 hours. After the reaction is completed, the liquid on the membrane surface is removed to complete the preparation of the amphoteric porous membrane.

[0019] Example 3: Using the following scheme S1: The PTFE membrane was cleaned with anhydrous ethanol to remove the grease and wax on the membrane surface. The cleaned membrane was naturally dried in the air. The dried membrane was placed in a vacuum oven with a power of 63W and an air flow of 30cm 3 / min plasma treatment equipment to carry out activation treatment, and after 115S, an activated PTFE membrane is obtained; S2: 3-mercaptopropyltriethoxysilane was dissolved in DMAc to prepare a grafting monomer solution with a mass concentration of 5%, and the activated PTFE membrane was immersed in the grafting monomer solution, and the grafting reaction was carried out at a temperature of 50°C. After 5 hours, the grafting reaction was completed, and the residual liquid on the membrane surface was removed. The grafted membrane was immersed in a hydrogen peroxide solution with a mass concentration of 20%, and an oxidation reaction was carried out at a temperature of 70°C. After 12 hours, the oxidation reaction was completed, and the residual liquid on the membrane surface was removed to obtain an acidic grafted PTFE membrane; S3: The acid-grafted PTFE membrane is immersed in a 6% mass concentration of 1,4-dimethyl-5-aminoimidazole hydrochloride aqueous solution for Schiff base reaction at 70° C. for 5 hours. After the reaction is completed, the liquid on the membrane surface is removed to complete the preparation of the amphoteric porous membrane.

[0020] Example 4: Using the following scheme S1: The PTFE membrane was cleaned with anhydrous ethanol to remove the grease and wax on the membrane surface. The cleaned membrane was naturally dried in the air. The dried membrane was placed in a vacuum oven with a power of 25W and an air flow of 10cm 3 / min plasma treatment equipment to perform activation treatment, and after 200S, an activated PTFE membrane is obtained; S2: 3-mercaptopropyltriethoxysilane was dissolved in DMF to prepare a grafting monomer solution with a mass concentration of 1%, and the activated PTFE membrane was immersed in the grafting monomer solution, and the grafting reaction was carried out at a temperature of 30°C. After 8 hours, the grafting reaction was completed, and the residual liquid on the membrane surface was removed. The grafted membrane was immersed in a potassium permanganate aqueous solution with a mass concentration of 10%, and an oxidation reaction was carried out at a temperature of 90°C. After 6 hours, the oxidation reaction was completed, and the residual liquid on the membrane surface was removed to obtain an acid-grafted PTFE membrane; S3: The acid-grafted PTFE membrane is immersed in a 2% mass concentration of 1,5-dimethyl-4-aminoimidazole hydrochloride aqueous solution for Schiff base reaction at 50° C. for 8 hours. After the reaction is completed, the liquid on the membrane surface is removed to complete the preparation of the amphoteric porous membrane.

[0021] Comparative Example 1: Adopt the following scheme The preparation process of this comparative example is different from that of Example 1 in that only step S1 is performed, and steps S2 and S3 are not performed. Figure 2 The infrared spectrum of the film prepared in this comparative example shows that the film after plasma treatment has a wavelength of 3300 cm -1 There is an obvious hydroxyl peak at , indicating that hydroxyl groups are successfully generated on the membrane.

[0022] Comparative Example 2: Adopt the following scheme The difference between the preparation process of this comparative example and that of Example 1 is that step S1 and step S2 are performed, but step S3 is not performed. Figure 3 This is the ZETA potential diagram of the membrane prepared in this comparative example. It can be seen from the potential diagram that the surface of the membrane after grafting mercaptosilane and oxidation has a negative charge.

[0023] Comparative Example 3: Adopt the following scheme The preparation process of this comparative example is different from that of Example 1 in that the oxidation part in steps S1 and S2 and step S3 are performed, and the grafting part in step S2 is not performed. Figure 4 This is the ZETA potential diagram of the membrane prepared in this comparative example. It can be seen from the potential diagram that the membrane surface grafted with aminoimidazole through the Schiff base reaction has a positive charge.

[0024] The amphoteric porous membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were stacked and tested under the same test conditions to record the coulombic efficiency, energy efficiency, voltage efficiency and capacity retention of the battery. The test results are shown in Table 1: Table 1 Performance test results of amphoteric porous membranes of examples and comparative examples

[0025] As can be seen from Table 1, compared with Comparative Example 1, Examples 1-4 have higher coulombic efficiency, energy efficiency, voltage efficiency and capacity retention rate.

[0026] Compared with Comparative Example 2, Examples 1 to 4 have higher coulombic efficiency and capacity retention rate. The mercaptosilane is grafted and cross-linked with the hydroxyl groups on the membrane surface to adjust the pore size of the porous membrane, hinder the penetration of vanadium ions, and improve the coulombic efficiency. By oxidizing the mercaptosilane, sulfonic acid groups are generated, the membrane is made negatively charged, which accelerates the proton transfer speed and also increases the migration rate of vanadium ions, resulting in a decrease in the coulombic efficiency and capacity retention rate.

[0027] Compared with Comparative Example 3, Examples 1 to 4 have higher voltage efficiency. By grafting aminoimidazole monomers on the membrane surface through a Schiff base reaction, the membrane surface is made positively charged, which not only hinders the migration of vanadium ions but also prevents the transmission of protons, thereby increasing the membrane surface resistance and causing a decrease in voltage efficiency.

[0028] Through comparison, it was found that the amphoteric porous membrane system used in all-vanadium liquid flow batteries has both acidic functional groups to ensure the transmission of protons and alkaline functional groups to block the passage of vanadium ions. It can have both low vanadium ion permeability and high proton transmission rate, thereby improving the battery's coulombic efficiency, energy efficiency, voltage efficiency and capacity retention rate.

[0029] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an amphoteric porous membrane for an all-vanadium liquid flow battery, characterized in that: Proceed as follows: S1. The polytetrafluoroethylene membrane is cleaned with anhydrous ethanol to remove grease and wax on the membrane surface, the cleaned membrane is naturally dried in the air, and the dried membrane is placed in a plasma treatment device for activation treatment in an air atmosphere to obtain an activated polytetrafluoroethylene membrane; S2, dissolving mercaptosilane in an organic solvent to prepare a grafting monomer solution, immersing the activated polytetrafluoroethylene membrane in the grafting monomer solution to carry out a grafting reaction, removing the residual liquid on the membrane surface after the reaction is completed, immersing the grafted membrane in an oxidant aqueous solution for oxidation, and removing the residual liquid on the membrane surface after the oxidation is completed to obtain an acidic grafted polytetrafluoroethylene membrane; S3, immersing the acidic grafted polytetrafluoroethylene membrane in an aminoimidazole solution to carry out a Schiff base reaction, and removing the liquid on the membrane surface after the reaction is completed, thereby completing the preparation of the amphoteric porous membrane.

2. The method for preparing an amphoteric porous membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S1, the activation treatment power is 25-100 W and the time is 30-200 s.

3. The method for preparing the amphoteric porous membrane for all-vanadium redox flow battery according to claim 1, characterized in that: In step S2, the mercaptosilane is one of 3-mercaptopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane, with a mass concentration of 1% to 9%; the organic solvent is one of N,N-dimethylacetamide and N,N-dimethylformamide; the oxidant is one of hydrogen peroxide and potassium permanganate, with a mass concentration of 10% to 30%.

4. The method for preparing an amphoteric porous membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: In step S2, the grafting reaction time is 2-8 hours, and the temperature is 30-60° C.; the oxidation reaction time is 6-18 hours, and the temperature is 50-90° C.

5. The method for preparing an amphoteric porous membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The aminoimidazole solution in step S3 is one of 1-(3-aminopropyl)imidazole solution, histamine solution, 1,4-dimethyl-5-aminoimidazole hydrochloride solution, and 1,5-dimethyl-4-aminoimidazole hydrochloride solution, and the mass concentration is 2% to 10%.

6. The method for preparing an amphoteric porous membrane for an all-vanadium redox flow battery according to claim 1, characterized in that: The grafting reaction time in step S3 is 2-8 hours, and the temperature is 50-90° C.

7. An amphoteric porous membrane for an all-vanadium liquid flow battery, characterized in that: The amphoteric porous membrane for all-vanadium redox flow battery is prepared by the method for preparing the amphoteric porous membrane for all-vanadium redox flow battery according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of amphoteric ion exchange membrane

    CN102181069A

  • Zwitter Nafion ion exchange membrane for vanadium batteries and preparation method thereof

    CN108695534A

  • Asymmetric porous membrane for all-vanadium redox flow battery and preparation method thereof

    CN118767697A

  • The method of removing metal from phthalocyanine pigment

    KR1020230129770A